A Comparison of Energy Efficiency in AC and DC Microgrid with New Energy. Issue 1 (December 2020) - HuipengLi,; Li, Shengwen; Wang, Tan; Wang, Xu; Chang, Xiao; Zhang, Min; Meng, Runquan
Abstract: As photovoltaic, wind power and other new energy sources are connected to the power grid on a large scale, the research on key technologies of microgrid needs to be further improved. Since most distributed generation and energy storage devices are mostly powered by direct current, DC distribution technology has got more and more attention. Aiming at the difference of energy efficiency between AC and DC microgrid, this paper proposes the analysis method of "the efficiency of source side with distributed generation", establishes a mathematical model of system loss of AC and DC microgrid with distributed generation and sets up a selection principle of distribution system mode through the intersection point of system loss rate, from the perspective of energy efficiency. The calculation results show that the loss rate of DC microgrid with distributed power source is lower than that of AC microgrid supposing the DC load ratio is 50%. The system loss rate curve confirms the necessity of DC distribution system technology research. With the continuous access of distributed generation and energy storage devices to microgrids, and the increasing improvement of DC load rate, the DC microgrid with distributed generation will have more advantages in the future.